PREVALENSI DAN ETIOLOGI KEBIASAAN MENGUNYAH SATU SISI PADA ANAK USIA 12-14 TAHUN - Wulandari, Veronica Veronica; Mahendra, Putri Kusuma Wardani; Bramanti, Indra (Universitas Baiturrahmah, 2024)
Introduction: The high prevalence of unilateral chewing behaviors can be influenced by pain, tooth radices, extracted teeth, food impaction, malocclusion, and others. Aim: This study aims to assess the prevalence and identify the etiology of unilateral chewing in children aged 12-14 years. Methods: Observational cross-sectional study was conducted among 211 students aged 12-14 at 2 junior high schools at Kecamatan Gamping. Chewing patterns were observed while they chewed gum for 15 seconds, paused, smiled widely, and repeated this process 7 times at 5-second intervals. Students were classified as having a consistent unilateral chewing habit if they consistently chewed on one side and predominant habit if they chewed 5-6 times on the same side. Furthermore, a clinical examination of the oral cavity was performed to assess the students' oral health. The data were analyzed descriptively and statistically using the chi-square test. Result: The findings revealed that 61.14% of the students exhibited a unilateral chewing habit and there were no significant differences between males and females. The consistent category is mostly caused by caries factor, while the dominant category is caused by non-caries factors. There were notable differences in the etiology between the consistent and dominant categories. Conclusion: The prevalence of unilateral chewing habits among students aged 12-14 was 61.14%. The primary etiology of consistent unilateral chewing was caries-related factors and predominant category was non caries factors